2012
DOI: 10.3349/ymj.2012.53.2.401
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 2 Infection Rate and Necessity of Screening during Pregnancy: A Clinical and Seroepidemiologic Study

Abstract: PurposeThis study determined the seroprevalence of herpes virus 2 in gravidas and the differences between herpes virus 2-infected and healthy gravidas. The need to screen gravidas for herpes virus 2 was also evaluated.Materials and MethodsA retrospective analysis involving 500 gravidas who underwent herpes virus 2 serologic testing and delivery in our hospital between January 2009 and August 2010 was performed. All patients in the study group were classified as herpes simplex virus 2 (HSV2) positive, and all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 36 publications
3
25
2
6
Order By: Relevance
“…15 Virus ini menyebabkan infeksi mukokutan, sistem saraf pusat dan kadang-kadang dapat mengancam jiwa. 9 Terdapat 2 tipe HSV yang berbeda secara genetik dan predileksi lesi yang ditimbulkan yaitu HSV-1 yang sering menyebabkan lesi di daerah orofasial dan ditularkan melalui kontak non seksual dan HSV-2 di daerah genital yang ditularkan melalui aktivitas seksual. Tetapi adanya perubahan pada perilaku seksual individu menyebabkan HSV-1 juga dapat menginfeksi daerah genital.…”
Section: Herpes Simplex Virusunclassified
See 3 more Smart Citations
“…15 Virus ini menyebabkan infeksi mukokutan, sistem saraf pusat dan kadang-kadang dapat mengancam jiwa. 9 Terdapat 2 tipe HSV yang berbeda secara genetik dan predileksi lesi yang ditimbulkan yaitu HSV-1 yang sering menyebabkan lesi di daerah orofasial dan ditularkan melalui kontak non seksual dan HSV-2 di daerah genital yang ditularkan melalui aktivitas seksual. Tetapi adanya perubahan pada perilaku seksual individu menyebabkan HSV-1 juga dapat menginfeksi daerah genital.…”
Section: Herpes Simplex Virusunclassified
“…5,11 Infeksi primer terutama pada herpes genitalis dalam kehamilan menimbulkan infeksi yang lebih berat pada neonatus, terlebih pada penderita yang belum memiliki antibodi terhadap HSV. 1,9 Infeksi HSV pada neonatus dapat diperoleh pada saat kehamilan, intrapartum, atau post partum. Risiko infeksi HSV intrauterin meningkat pada ibu hamil yang menderita infeksi HSV yang meluas dimana 90% disebabkan oleh HSV-2.…”
Section: Infeksi Hsv Pada Saat Kehamilanunclassified
See 2 more Smart Citations
“…There are several factors related to spontaneous abortion, such as genetic abnormalities and infections (3) . Many studies showed virus such as human cytomegalovirus (HCMV), human herpes simplex virus (HHSV-1/2), human parvovirus B19 (B19V), enterovirus, adenovirus, and varicella-zoster virus are causative agents of spontaneous abortion (4)(5)(6) . Herpesviruses comprise the largest family of viruses with oral manifestations.…”
Section: Introductionmentioning
confidence: 99%